Influence of cutting tool vibrations on the surface quality of cut sheet materials and methods for their minimization - Zenkin, Mykola; Ivanko, Andrii; Chernysh, Maksym (INNOVATIVE TECHNOLOGIES AND SCIENTIFIC SOLUTIONS FOR INDUSTRIES, 2025)
The subject of the study is the influence of cutting tool vibrations on the surface quality of cut sheet materials during mechanical processing, as well as the analysis of the mechanisms of vibration occurrence and the development of methods for their minimization to increase the efficiency of technological operations in mechanical engineering. The purpose of the work is to develop scientifically based approaches to predicting the resource of cutting tools and optimizing cutting modes by reducing vibration loads, which will allow to improve the quality of surface processing of sheet materials, reduce production costs and prevent processing defects. Tasks: assessment of the vibration characteristics of the tool depending on the cutting modes and the degree of wear; analysis of the influence of vibrations on surface roughness and defects (waviness, microcracks); development and testing of vibration minimization methods, including damping systems and ultrasonic vibrations; determination of optimal processing conditions for various materials. Methods: experimental analysis using accelerometers for three-axis vibration monitoring; profilometry and microscopy for surface quality assessment; stochastic modeling of tool wear based on statistical data; testing of damping systems (elastic couplings, dampers) and ultrasonic vibrations (20–30 kHz); comparative analysis of the effectiveness of lubricating and cooling fluids. Research results: it was found that vibrations along the X axis have the greatest impact on the formation of surface defects, especially with increasing cutting depth and tool wear; ultrasonic vibrations (22 kHz, amplitude 10 μm) reduce friction and stabilize the cutting process, improving the quality of machined surfaces; damping systems effectively reduce the amplitude of vibrations at critical frequencies (up to 1.5 kHz); the use of water as a coolant turned out to be more effective than copper oil, reducing surface irregularities; an improved model of an end mill with damping elements was developed, which reduces vibration loads and defects when processing thin-sheet materials. Conclusions: the conducted studies show that vibration monitoring is an effective tool for diagnosing the condition of the cutting tool and optimizing the cutting process; the integration of damping systems and ultrasonic vibrations allows you to significantly reduce vibration effects, improve the surface quality of sheet materials and extend the tool life, which contributes to the economic efficiency of production and minimizing processing defects.